LYMPH NODE METASTASIS FROM SOFT TISSUE SARCOMAS: INCIDENCE OF METASTATIC SPREAD, RISK FACTORS, MECHANISMS OF OCCURRENCE - N. V. Vasilyev (Сибирский онкологический журнал)
The review presents the most recent data on the incidence and pathogenesis of lymph node metastasis from soft tissue sarcoma, a very rare clinical event.